The Effect of Using Wordwall Media on Reading Skills and Comprehension of Narrative Text - Rahayu, Enny; Nurdilla, Nurdilla; Ramadhani*, Sri (Universitas Syiah Kuala, 2024)
This research was motivated by the lack of reading comprehension of fourth grade students at SDS An Najwa Marelan in narrative text material. This is because teachers have not implemented learning media and students do not understand reading narrative texts. As a result, students feel bored reading the text and find it difficult to come up with ideas for paragraphs and the content of the story. The aim of this research is to describe the use of wordwall media and find out whether there is an influence of wordwall media on the ability to read and understand narrative text. This type of research is quantitative research, the data collection method used is a questionnaire. The research results show that there is an influence of using wordwall media in improving reading comprehension skills in determining the main idea in each paragraph, searching for information and understanding the content of the story and retelling the story using their own language. Thus, the reading comprehension skills of class IV SDS an Najwa Marelan students in narrative text material show improvement through wordwall media